Molar incisor hypomineralization in North Malabar: An epidemiological study - Faizal C Peedikayil; Nitya C Tomy; T P Chandru; Mahmood Muthedath; Jerin Jose (Wolters Kluwer Medknow Publications, 2019)
Background and Objectives: Molar incisor hypomineralization (MIH) is an acquired developmental defect of unknown etiology. The acquired factors include perinatal events, exposure to fluoride, infantile exposure to biphenols and dioxins, childhood illness, specific chronic disease. A study was conducted in two districts, namely Kannur and Kasaragod district of Kerala to know the prevalence of molar incisal hypomineralization. Materials and Methods: A cross-sectional epidemiological study was conducted on a random sample of 2000 normal - healthy school children aged between 6 and 10 years of Kannur and Kasaragod district of Kerala. A full mouth inspection of wet teeth was performed for all the examined children using the 10-point scoring system which is in accordance with the European Academy of Paediatric Dentistry evaluation criteria. Data were collected, recorded, tabulated, and evaluated using the Statistical Package for the Social Sciences 17.0 for Windows. Percentage arithmetic mean value, standard deviation, independent sample t-test, Chi-square test, and Pearson correlations were used while a P< 0.05 was considered statistically significant. Results: The study result showed the prevalence of MIH as 19.8% in children of age group 6-10 years in northern Kerala. The prevalence in Kannur and Kasaragod districts were 16% and 23.6%, respectively. Interpretation and Conclusion: Prevalence of Molar Incisor Hypominerilization is more in Kasaragod district. Therefore, more studies should be done to confirm the effect of environmental factors in those areas.